2009
DOI: 10.1016/j.nbd.2009.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Response of aged parkinsonian monkeys to in vivo gene transfer of GDNF

Abstract: This study assessed the potential for functional and anatomical recovery of the diseased aged primate nigrostriatal system, in response to trophic factor gene transfer. Aged rhesus monkeys received a single intracarotid infusion of MPTP, followed one week later by MRI-guided stereotaxic intrastriatal and intranigral injections of lentiviral vectors encoding for glial derived neurotrophic factor (lenti-GDNF) or beta-galactosidase (lenti-LacZ). Functional analysis revealed that the lenti-GDNF, but not lenti-LacZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
1
42
1
Order By: Relevance
“…Preclinical studies using viral vector-mediated gene transfer have been successful in ameliorating symptoms and rescuing nigral dopamine neuron loss in PD models (Emborg et al , 2009; Gash et al , 1996; Gasmi et al , 2007; Gombash et al , 2012; Herzog et al , 2008; Kordower et al , 2000), yet human clinical trials have not experienced similar success (Bartus et al , 2011; ClinicalTrials.gov, 2013; Marks et al , 2010; Stocchi and Olanow, 2013). This discrepancy may be, in part, attributable to the almost exclusive use of young adult animals in preclinical studies that fail to recapitulate the aged host brain environment typical of most PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies using viral vector-mediated gene transfer have been successful in ameliorating symptoms and rescuing nigral dopamine neuron loss in PD models (Emborg et al , 2009; Gash et al , 1996; Gasmi et al , 2007; Gombash et al , 2012; Herzog et al , 2008; Kordower et al , 2000), yet human clinical trials have not experienced similar success (Bartus et al , 2011; ClinicalTrials.gov, 2013; Marks et al , 2010; Stocchi and Olanow, 2013). This discrepancy may be, in part, attributable to the almost exclusive use of young adult animals in preclinical studies that fail to recapitulate the aged host brain environment typical of most PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…CED-based in vitro, ex vivo and in vivo animal models have led to active genetherapy trials for treating Parkinson disease (PD)and are supported by histological studies on disease pathology [9].Use of MRI navigation in some clinical trials, helps accurately targeting and providing real time monitoring of viral vector delivery (rCED). Several researcher labs including ours adopted different small and large animal models exploring use of CED in brain [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The results from these studies are promising with a suggestion of superiority over intrathecal (IT) injection.…”
Section: Additionally There Is a Need To Visualize Target And Contrmentioning
confidence: 99%
“…4 which may overcome these disadvantages, is the use of gene therapy to deliver the gene for IGF-1 through a viral vector system. Numerous reports have shown both efficient and stable expression of GDNF from lentiviral vectors (LVs) in pre-clinical animal models of PD [23][24][25][26][27] . We have previously demonstrated that the novel integration-deficient LVs (IDLVs) are as efficient as their standard integration-proficient counterparts (IPLVs) at transducing rodent eye and brain cells in vivo 28 but have enhanced biosafety due to their reduced risk of insertional mutagenesis 28,29 .…”
Section: Page 3 Of 40mentioning
confidence: 99%